Diseño e implementación de un sistema de gestión para el manejo de la información de los equipos biomédicos de la clínica odontológica de la UAN sede Bogotá Circunvalar (2023)
The equipment documentation for biomedical devices used in dental diagnosis, prevention, treatment, and rehabilitation at the Circunvalar branch of the University Antonio Nariño's dental clinic was updated in compliance with Resolution 3100 of 2019, following the guidelines for equipping biomedical equipment. The project employed the waterfall methodology, encompassing eight sequential stages, from requirements analysis to the delivery of a comprehensive management system designed in LibreOffice Base.